Analysis of Nutrient Content in Bangke Cake with the Addition of Brown Rice Flour - Lydia Fanny; Thresia Dewi Kartini B (Humanistic Network for Science and Technology (HNST), 2022)
Efforts to provide additional food to cronic lack of energy pregnant women aim to increase the intake of macro and micro nutrients (iron and vitamin A). Bangke cake is one of the traditional Indonesian pastries in South Sulawesi Province. Knowing the acceptability and analysis of macro and micro nutrients content in macro and micro nutrients in Bangke cake with the addition of brown rice flour. The assessment method uses 4 hedonic scales and the criteria for the panelists selected to perform the hedonic test are untrained panelists consisting of 50 pregnant women. The data from the test results of nutrient levels were analyzed by two-way ANOVA test and the data from the organoleptic test results, namely the hedonic test on acceptability was analyzed by the Kruskal Wallis test. The brown rice flour substitution cake that was most acceptable to panelists from all aspects was the F3 formula. Nutrient levels in the brown rice flour substitution showed an increasing trend of nutrient levels of macro nutrients and beta-carotene, except for iron.Keywords: brown rice; bangke cake; pregnant women; chronic energy deficiency